(rev.) Marc Lynch, The Arab Uprising: The Unfinished Revolutions of the New Middle East, Public Affairs, New York 2012 - Jarząbek, Jarosław (The Copernicus Journal of Political Studies, 2018)
Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14763